2009
DOI: 10.3758/app.71.1.156
|View full text |Cite
|
Sign up to set email alerts
|

Spatial acuity and summation on the hand: The role of thermal cues in material discrimination

Abstract: The spatial characteristics of thermal perception were studied in two experiments that examined how thermal stimuli are processed within the hands. A thermal display that simulates cues associated with making contact with different materials was used in these studies. In the first experiment, participants indicated which of two simulated materials that were presented to the index fingertip was cooler. The results indicated that participants were unable to resolve the two areas of thermal stimulation. In the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…Although our data provide no evidence for a dependency of the thermal gradient on the four tested configurations, all subjects were able to perceive a thermal gradient (two distinct temperatures) at the level of the fingertip. This finding is novel as previous research reported no capability to discriminate two different, adjacent, materials through thermal stimulation only (Yang et al, 2009). The divergence between the results might be due to the difference of the thermal stimulations.…”
Section: Thermal Feedback To Convey Encoded Information At the Fingertipcontrasting
confidence: 51%
See 2 more Smart Citations
“…Although our data provide no evidence for a dependency of the thermal gradient on the four tested configurations, all subjects were able to perceive a thermal gradient (two distinct temperatures) at the level of the fingertip. This finding is novel as previous research reported no capability to discriminate two different, adjacent, materials through thermal stimulation only (Yang et al, 2009). The divergence between the results might be due to the difference of the thermal stimulations.…”
Section: Thermal Feedback To Convey Encoded Information At the Fingertipcontrasting
confidence: 51%
“…Although this might be related to previous research showing that two distinct materials cannot be discriminated under one single fingertip based on thermal cues alone (Yang et al, 2009), no study has yet investigated whether several distinct and constant temperatures can be differentiated under the fingertip. This may be of great importance for novel applications of thermal interfaces such as using the display to present scalar, non-thermal information to the user under the form of encoded thermal stimuli (Zerkus et al, 1994;MacLean and Roderick, 1999).…”
Section: Gallo Et Al Encoded and Crossmodal Thermal Stimulationmentioning
confidence: 77%
See 1 more Smart Citation
“…To improve the accuracy of the thermal response prediction, studies have proposed models that consider the effect of metabolic heat generation and blood perfusion 38-41 or divide the skin into several layers based on its anatomical structure. 9,41-43 To date, various thermal models have been proposed for modeling the heat transfer process during hand-object interactions (for a full review, see ref.…”
Section: Physical Processmentioning
confidence: 99%
“…Many thermal tactile displays have been developed to evaluate the importance of thermal cues in object identification and discrimination [2][3][4]. These displays mainly consist of a Peltier device, temperature sensors and a temperature-control system that monitors and controls the surface temperature of the device [5].…”
Section: Introductionmentioning
confidence: 99%